Buyer-supplier collaboration and supply chain resilience: a case study in the petrochemical industry - Kotzé, T.; Botes, A.; Niemann, W. (South African Journal of Industrial Engineering, 2017)
The purpose of this study was to investigate the underlying mechanisms through which buyer-supplier collaboration enables resilience. A single case study method was adopted, examining a critical case within the petrochemical industry. Data was collected through semi-structured interviews. The rationale for undertaking buyer-supplier collaboration in the focal firm is grounded in Kraljic’s procurement matrix, accounting for underlying risks of supply disruptions that are inherent in the resilience discourse. The findings suggested that collaboration between buyers and suppliers does not directly lead to supply chain resilience, but rather enables the antecedents to supply chain resilience. The study developed an understanding of the specific mechanisms through which the antecedents of resilience are enabled in the petrochemical industry. Die doel van hierdie studie was om die onderliggende meganismes waardeur koper-leweransier samewerking veerkragtigheid in staat stel, te ondersoek. ’n Enkele gevallestudie metode was gebruik om ’n kritiese geval in die petrochemiese bedryf te ondersoek. Data-insameling het plaasgevind deur middel van semi-gestruktureerde onderhoude. Die rasionaal om die koper-leweransier samewerking in die geval te onderneem is gegrond in Kraljic se verkrygingsmatriks. Laasgenoemde neem onderliggende risiko’s van die lewerings-ontwrigting, wat inherent is aan die veerkragtigheid diskoers, in ag. Die bevindinge dui daarop dat samewerking tussen kopers en leweransiers nie direk lei tot voorsieningsketting veerkragtigheid nie, maar dat dit eerder die voorlopers tot voorsieningsketting veerkragtigheid in werking stel. Die studie ontwikkel begrip vir die spesifieke meganismes waardeur die voorlopers tot veerkragtigheid in die petrochemiese bedryf in staat gestel word.